Her best-kept secret : why women drink -- and how they can regain control - Glaser, Gabrielle (New York : Simon & Schuster, 2013)
Looks at the cultural factors contributing to a rise in alcoholism among today's women and compares today's practices to those of earlier generations while noting the current ineffectiveness of AA and other mainstream treatments.
Lush -- We are women, hear us pour -- I have to see a man about a dog -- One day at a time : A.A. and women -- Rehab nation -- The thirteenth step -- Twenty-first century treatment.
Includes bibliographical references (pages [189]-228) and index.
Keywords: Women -- Alcohol use -- United States; Women alcoholics -- Rehabilitation -- United States